Fabrication And Characterization Of Bioactive Glassalginate Scaffolds - Mohd Anuar, Siti Nur Nabilah (Universiti Sains Malaysia, 2018)
Tissue engineering evolved from the field of biomaterials development and refers to the practice of combining scaffolds, cells and biologically active molecules into functional tissues. The goal of tissue engineering is to assemble functional constructs that restore, maintain or improve damaged tissues or whole organs. Bioactive glass is one type of biomaterials where its development has influenced human lives to a large extent by its versatile medical applications and very promising future. In this present study, 45S5 type of bioactive glass (BG) was used together with mineral cordierite and oxide cordierite to fabricate scaffolds through freeze drying method. The scaffolds were fabricated through freeze-drying technique by pre-freezing 20 gram of slurry for each composition (15 gram 45S5 BG + 5 gram mineral cordierite and 15 gram 45S5 BG + 5 gram oxide cordierite) with subjected pre-freezing temperature; -10oC and -40oC. This fabrication was fabricated in order to study the effect of mineral and oxide cordierite to 45S5 BG and the effect of different pre-freezing temperature to the mineral cordierite45S5 and oxide cordierite-45S5 scaffolds. Compression and porosity test were done and scaffold with 15 gram 45S5 + 5 gram oxide cordierite with -40oC of pre-freezing temperature give the highest percentage of porosity hence the compression test is the lowest. The same scaffold was coated with 5 wt.% concentration of sodium alginate to study the effect of sodium alginate on mechanical properties of the scaffold. Result from the compression test shows that the strength of the scaffold coated with sodium alginate is higher compared to the uncoated scaffold with value of 0.037 MPa and 0.01 MPa for uncoated oxide cordierite-45S5 scaffold with pre-freezing temperature -40oC.